Analysis of endemic South African HIV-1 isolates using anti-GP 120 aptamer(s) - Mufhandu, Hazel Tumelo (My University, 2014)
The HIV-1 epidemic in South Africa remains the highest worldwide with subtype C as the major circulating virus. An HIV vaccine is still elusive, and with only half of the infected population receiving antiretroviral treatment, the demand for comprehensive interventions such as the development of new therapeutic agents is indispensable. It was previously shown that a parental anti-gp120 RNA aptamer, called B40, neutralized a broad range of HIV-1 subtypes and suppressed viral replication in cultured human peripheral blood mononuclear cells by up to 10,000- fold. Therefore, in this study I explored the use of its modified synthetic derivative, called UCLA1, to neutralize HIV-1 subtype C clinical isolates. UCLA1 was shown to have high affinity for the consensus HIV-1 subtype C gp120 and neutralized subtype C isolates with IC50 values in the nanomolar range. There was no neutralization preference noted between viruses isolated from acute and chronic infections or between isolates from adult and paediatric patients in TZM-bl cells, PBMC or macrophage assays. The aptamer was not strain or tropism restricted since it neutralized both R5 and X4 viruses. It was also non-cytotoxic when tested in different cell lines. Mapping of UCLA1 binding sites on gp120 revealed eight amino acid residues that modulated neutralization resistance. These included residues within the co-receptor binding site, at the base of the V3 loop, and in the bridging sheet within the conserved V1/V2 stem-loop of gp120. The aptamer was also shown to have synergistic effects with T20, a gp41 fusion inhibitor and IgG1b12, an anti-CD4 binding site monoclonal antibody. Two primary viruses were tested for their ability to become resistant by culturing them under escalating concentrations of the aptamer for a maximum of 84 days. Only one of the two viruses mutated to escape neutralization by UCLA1 at 7-fold of the IC50. Six escape mutations were identified within the V3 loop and in the CD4 and co-receptor binding complex at the base of the β15 sheet and the α3 helix, confirming and extending UCLA1 binding sites mapping data. Taken together, these data show that UCLA1 has broad spectrum potency as an entry inhibitor against HIV-1 subtype C isolates suggesting it might be a suitable candidate for human clinical testing with a low propensity for developing resistance.